A bibliometric analysis of road traffic injury research themes, 1928–2018. Issue 2 (3rd April 2021) - Jing, Linlin; Shan, Wei; Zhang, Yingyu
Abstract: Road traffic accidents have become an important social issue worldwide. This study aims to analyse the research status of road traffic injury from 1928 to 2018 and discuss the future research trends. Co-word analysis was applied to analyse 4, 184 articles collected from the core collection of Web of Science. Cluster analysis and social network analysis (SNA) were adopted to group keywords, visualize the links between them, and indicate their importance. Strategic diagram was used to reveal the network status of each cluster. The results lead to the following conclusions: (1) 'Road traffic accident', 'injury', 'road safety', 'mortality', and 'risk factor' are at the centre of social network, indicating that these keywords play the most important roles in the field of road traffic injury research. (2) A total of 60 high-frequency keywords are divided into five clusters, namely 'accident causes leading to injury', 'analysis methods', 'health & injury', 'safety management', and 'road traffic', indicating that they are the main sub-fields of road traffic injury research. (3) 'Risk perception' and 'systems theory' are widely discussed topics emerging in recent years. On the basic of the five clusters, valuable references are provided for future research.